Analysis on Long-Term Emission and Reduction Potential of Greenhouse Gases in the Industrial Sector of Seosan City of Korea Using Long-Range Energy Alternatives Planning Model - Chung, Jindo; Yoon, Sangwook (Asian Journal of Chemistry, 2014)
In this study, greenhouse gases emissions and reduction potentials were predicted using the long-range energy alternatives planning model mainly for industrial sector in Korea’s Seosan city that has a large consumption structure of energy. Energy consumption and greenhouse gases emissions were also predicted through the analysis of four scenarios resulting from the application of the reduction effect according to the basic energy plan and technology options of petrochemical industries. In scenario I, the policy of the national basic energy plan was analyzed which showed an improvement of energy basic by an annual average of 2.6 % until 2030. Scenario I showed the effect of reducing greenhouse gases emissions of 18.23 %, 297.2 thousand tCO2; scenario II, about 14 % in 2030 over 2005. It was analyzed that scenario III showed a reduction of 8 %, 135 thousand tCO2 compared to the baseline scenario; scenario IV showed a reduction of about0.2 % in greenhouse gases emissions. Accordingly, based on the result of the 0.75 % scenario which is commonly used as the annual average efficiency improvement rate of energy, the 30 % reduction of greenhouse gases emissions was analyzed to be a difficult goal until 2020, the baseline of the response measures to climate change of Seosan city compared to 2005 emissions.